The role of the gut microbiota and the nicotinate/nicotinamide pathway in rotenone-induced neurotoxicity - Yan Sai; Wei Ge; Li Zhong; Qifu Zhang; Jingsong Xiao; Yaohui Shan; Wenqi Ye; Haoyin Liu; Shulin Liu; Feng Ye; Xiaogang Wang; He Tang; et al. (Current Research in Toxicology)
Rotenone is a natural compound from plants. It is widely used in pesticides because of highly toxic to insects and fish. However, lots of research has reported that rotenone has neurotoxic effects in humans. It is confirmed there is a correlation between rotenone exposure and Parkinson’s disease (PD). Therefore, the role of gut microbiota and related metabolic pathways was investigated in rotenone-induced neurotoxicity. The results showed that the abundance of gut microbiota changed significantly. The differential metabolites were enriched in the nicotinate and nicotinamide metabolism pathways, which had the greatest impact on the entire metabolic system. The contents of acetic acid and butyric acid in intestinal tissues decreased significantly. Additionally, Interleukin-6 (IL-6), Tumor necrosis factor alpha (TNF-α) and vasoactive intestinal peptide (VIP) were significantly up-regulated, while gastrin (GAS) and Ghrelin were significantly down-regulated. Expression of intestinal tight junction protein was significantly reduced. Moreover, nicotinamide adenine dinucleotide (NAD+), a the product of the nicotinate/nicotinamide pathways, decreased significantly. And the expression levels of nicotinamide phosphoribosyl transferase (NAMPT) and Solute Carrier Family 25 Member 51 (SLC25A51) also reduced significantly. Therefore, gut microbiota was influenced obviously in rats exposed to rotenone, leading to a decrease of acetic acid and butyric acid contents, which might in turn affect the change of intestinal barrier permeability and induce inflammatory reactions. Meanwhile, the nicotinate/nicotinamide metabolic pathways might play an important role in rats exposed to rotenone.